The Thickness of Endometrium after Given Fennel Seed Extract (Foeniculum Vulgare M.) and Mimba Leaves (Azadirachia Indica Juss): Experimental Study on Female Mice - Isnu Kurnia Nugrahaeni; Melyana Nurul Widyawati; Noviyati Rahardjo Putri; Aida Amalia Nur Ramadhian; Beniqna Maharani Besmaya; Diksi Laksmita Dewi (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
Total Fertility Rate (TFR) in Indonesia is 2.6. It’s above the average TFR in ASEAN countries which is 2.44. This condition shows that Indonesia's population growth is high. The herbal plants as an alternative is a safe method of contraception that can reduce the negative effects of using hormonal contraceptives method. The safe method contraception using herbal plants can reduce the negative effects in using hormonal contraceptives. The aim of this study is to determine the changes in endometrial thickness due to the administration of Foeniculum Vulgare M. and Azadirachia indica Juss extracts. The type of this study is a true experimental design with Post Test Only Control Group Design. The subjects were 15 female mice (mus musculus) which were taken randomly and it divided into 3 groups, there were K- (standard care), K+ (contraceptive pills), and E (fennel seed extract and neem leaves extract with a dose of 7.84: 11.2 mg / 20g BW). The treatment was given for 14 days. On the 15th day, the mice were terminated to measure the thickness of the endometrium. The result of the study were analyzed using the ANOVA test and the post hoc Scheffe test. The results study shown that the administration of fennel seed and neem leaf extract had a significant effect in reducing endometrial thickness (p-value 0.05) so that it was proven to have an anti-fertility effect.